Aeromonas cavernicola sp. nov., isolated from fresh water of a brook in a cavern - Martínez-Murcia, Antonio; Beaz-Hidalgo, Roxana; Svec, Pavel; Saavedra, Ma José; Figueras, Ma José; Sedlacek, Ivo (Current microbiology, 2013)
Aeromonas P2973 was isolated from the water of a brook in a cavern in the Czech Republic. This isolate could not be biochemically identified at the species level, considering all updated species descriptions. Subsequent extensive phenotypic characterisation, DNA-DNA hybridisation, 16S rRNA gene sequencing and a Multi-Locus Phylogenetic Analysis (MLPA) of the concatenated sequence of 7 housekeeping genes (gyrB, rpoD, recA, dnaJ, gyrA, dnaX and atpD; 4705 bp) was employed in an attempt to ascertain the taxonomy of this isolate. Based on this polyphasic approach, we describe a novel species of the genus Aeromonas, for which the name Aeromonas cavernicola sp. nov. is proposed, with strain CCM7641(T) (DSM24474(T), CECT7862(T)) as the type strain.
Keywords: Microscopy, Electron, Transmission; Caves; Molecular Typing; ribozomální DNA; DNA, Ribosomal; DNA bakterií; jeskyně; bakteriální proteiny; Bacterial Proteins; RNA, Ribosomal, 16S; DNA, Bacterial; shluková analýza; Molecular Sequence Data; hybridizace nukleových kyselin; molekulární typizace; Fresh Water; Phylogeny; molekulární sekvence - údaje; sladká voda; Czech Republic; Bacterial Typing Techniques; Sequence Analysis, DNA; Nucleic Acid Hybridization; techniky typizace bakterií; Česká republika; transmisní elektronová mikroskopie; sekvenční analýza DNA; Cluster Analysis; fylogeneze; Aeromonas; RNA ribozomální 16S